The Hebb Synapse Before Hebb: Theories of Synaptic Function in Learning and Memory Before Hebb (1949), With a Discussion of the Long-Lost Synaptic Theory of William McDougall - Brown, Richard E.; Bligh, Thaddeus W. B.; Garden, Jessica F. (Frontiers in Behavioral Neuroscience, 2021)
Since the work of Semon was ‘rediscovered’ by Schacter in 1978, there has been a renewed interest is searching for the “engram” as the locus of memory in the brain and it has become popular to equate Hebb's cell assembly with Semon's engram. There have been many theories of memory involving some concept of synaptic change, culminating in the "Hebb Synapse" theory in 1949. However, Hebb said that the idea that any two cells or systems of cells that are repeatedly active at the same time will tend to become ‘associated’, was not his idea, but an old one. In this paper we give an overview of some of the theories of the neural basis of learning and memory before Hebb and describe the synaptic theory of William McDougall, which appears to have been an idea ahead of its time; so far ahead of its time, it was completely ignored by his contemporaries. We conclude with some comments by those who did not ignore McDougall’s theories and a short discussion on the fate of neuroscientists whose ideas were ignored when first presented, but were accepted as major insights many decades later.